PERSON CENTERED THERAPY SEBAGAI UPAYA PEMULIHAN KONSELI ALIENASI - As’ad; Moh. Hafid (Fakultas Dakwah Universitas Ibrahimy, 2023)
Alienation is a social disorder. An indicator of alienation is when a person experiences powerlessness towards his environment and is trapped in alienation. The subject of this study was an 18-year-old female counselee with alienation disorder. Subjects experience alienation in their social conditions. Person Centered Therapy is present by prioritizing providing comfort for the subject to tell stories and describe their problems and express their feelings. This comfortable condition in therapy is used as capital to change the condition of the subject who seems uncomfortable and even suspicious of the new environment which is his social transition from the old environment. This research is a type of action research which is divided into three cycles in its application. After the subject is well aware of his condition and abilities, then the subject is encouraged to be open to his new environment in order to optimize his potential back to normal. The results of this study obtained that person-centered therapy is able to be a means for subjects to recover their condition.